KKN Covid-19 UNS: Collaboration To Increase Digital Literation For Covid-19 Spreading Awareness - Sangka, Khresna Bayu (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Covid-19 pandemic has affected higher education, the implementation of Real Work Lectures (KKN) is carried out in accordance with government policies, work and school from home. Covid KKN - 19 Universitas Sebelas Maret (UNS) is conducted independently for the environment in which participating students live by utilizing the latest information media. The increase in digital literacy is used as an indicator to measure people's welfare. The series of activities in addition to providing increased digital literacy of citizens regarding the use of social media properly, correctly and wisely also provides increased awareness of the danger of plague. This activity proved to be very successful in terms of participants' participation and enthusiasm. Some key things that became the main points of the success of this collaboration include effective communication between members, collaboration between participants and citizens to understand and protect their families and the surrounding environment, as well as the desire to share the goodness with one another.